A fingerprint and finger-vein based cancelable multi-biometric system. (June 2018) - Yang, Wencheng; Wang, Song; Hu, Jiankun; Zheng, Guanglou; Valli, Craig
Highlights: Fingerprint and finger-vein based cancelable multi-biometric template design. Flexible feature-level fusion strategy with three fusion options. Enhanced partial discrete Fourier transform based non-invertible transformation. High-performing cancelable multi-biometric templates with strong security. Abstract: Compared to uni-biometric systems, multi-biometric systems, which fuse multiple biometric features, can improve recognition accuracy and security. However, due to the challenging issues such as feature fusion and biometric template security, there is little research on cancelable multi-biometric systems. In this paper, we propose a fingerprint and finger-vein based cancelable multi-biometric system, which provides template protection and revocability. The proposed multi-biometric system combines the minutia-based fingerprint feature set and image-based finger-vein feature set. We develop a feature-level fusion strategy with three fusion options. Matching performance and security strength using these different fusion options are thoroughly evaluated and analyzed. Moreover, compared with the original partial discrete Fourier transform (P-DFT), security of the proposed multi-biometric system is strengthened, thanks to the enhanced partial discrete Fourier transform (EP-DFT) based non-invertible transformation.